Anglo-Saxon verbs of sounds: Semantic architecture, lexical representation and constructions - Cortes Rodriguez, Francesco J.; Gonzalez Orta, Marta (Adam Mickiewicz University, 2006)
This paper provides a detailed analysis of the semantic structure of Anglo-Saxon verbs of sound from the point of view of the Lexical Grammar Model (LGM). Firstly, a description of the theoretical foundations of the LGM for the analysis of lexical structures and the specific methodological principles developed for historical vocabularies will be provided. Secondly, the semantic architecture of the verbal domain of Old English sound predicates will be offered. Thirdly, the system of lexical decomposition proposed by the LGM and its application to the lexical class under study will be explained. This system has the format of a lexical template which will be fundamental to understand the linking algorithm that mediates between the semantic representation of sound predicates and their morpho-syntactic realizations. This linking process has two phases: the first one will bind the lexical template of verbs of sound with the representation of the constructions and alternations where these predicates appear whereas the second interface will account for their grammatical behaviour.